HUBUNGAN PENGGUNAAN MEDIA SOSIAL DI INDONESIA DENGAN PENDEKATAN COMMUNICATION PRIVACY MANAGEMENT (CPM) GUNA MENINGKATKAN SELF DISCLOSURE ON SOCIAL MEDIA - Lulu Maulitha Al Rasyid; Yolanda Masnita (EBID: Ekonomi Bisnis Digital, 2024)
This research is motivated by the fact that many social media are used very widely in the context of Self Disclosure which can fulfill the emotions of users on social media, but is accompanied by risks that can be detrimental to the user. The aim of this research is to provide knowledge, understanding and information about problems for users of social media platforms (Facebook, Instagram, Twitter (X), Tiktok, Youtube) in Indonesia. A total of 130 respondents participated in the survey who were users or who had used social media in Indonesia. Data were processed and analyzed using SPSS and AMOS using Structural Equation Modeling (SEM).